Remixing the curriculum : the teacher's guide to technology in the classroom - Keefe, Elizabeth Stringer, 1972-; Steiner, Adam, 1973- (Rowman & Littlefield, a wholly owned subsidiary of The Rowman & Littlefield Publishing Group, Inc., 2018)
Remixing the Curriculum suggests that the way to develop curriculum to maximize student access and engagement is to employ essential elements of traditional pedagogy, but infuse it with technology to create new features through the Technology Fitness, Proactive Teaching, Universal Design for Learning, and Assistive Technology.